Sed & awk pocket reference - Robbins, Arnold (O'Reilly, 2002)
For people who create and modify text files, sed and awk are power tools for editing. sed, awk, and regular expressions allow programmers and system administrators to automate editing tasks that need to be performed on one or more files, to simplify the task of performing the same edits on multiple files, and to write conversion programs. The sed & awk Pocket Reference is a companion volume to sed & awk, Second Edition, Unix in a Nutshell, Third Edition, and Effective awk Programming, Third Edition. This new edition has expanded coverage of gawk (GNU awk), and includes sections on:An overview o.
"Text processing with regular expressions"--Cover. - Includes bibliographical references (page 46). - Print version record
Keywords: UNIX (Computer file); Sed (Computer file); Awk; Utilities (Computer programs); Utilitaires (Logiciels); COMPUTERS; Operating Systems; Linux; COMPUTERS; Operating Systems; UNIX; COMPUTERS; System Administration; Linux & UNIX Administration